Changes in restored soils subject to weathering and their implication in Mexican environmental regulations - Méndez-Moreno, José del C.; De la Garza-Rodríguez, Iliana M.; Torres-Sánchez, Sonia A.; Jiménez-Pérez, Nelly del C.; Sánchez-Lombardo, Irma; López-Martínez, Sugey; Lobato-García, Carlos E.; Morales-Bautista, Carlos M. (REVISTA TERRA LATINOAMERICANA, 2021)
An overview of current Mexican legislation regarding soil restoration and updating needs is made through the analysis of three case studies located in the southeastern México: a) soil affected by spillage of congenital waters (Zone 1), b) soil contaminated by hydrocarbons (Zone 2) and, c) a site adjacent to urban infrastructure (Zone 3). It was performed a comparative analysis of the soils conditions in the short and long term after the anthropogenic impact and restoration process that were carried out in each studied location. It was found that important properties of the soils do not recover after the weathering process, for instance in Zone 1, DR and DA as well as %Po did not reach equivalent values to the control sample and the soil texture is different even after a long recovery period. For Zone 2, it was detected important variations in the concentration of Ca, Na and K in both the impacted and recovered soils which affect the growth of plantations. In Zone 3, there were found signif icative differences in DA, %Po; %L, %R, %MO and CEC parameters. The current normative considers general aspects, but does not contemplate the actual site situation, there is an information gap due to this, although it was observed achievement of physical and chemical properties for the recovery soil use in each site, it was also noticed that the evaluations do not consider if these properties can change over time due to weather conditions, therefore, they could influence the success of each restoration process in the long term. The information generated can be used to make decisions about government rescue programs for the primary sector or as a starting point in the implementation of Environmental Bases Lines (LBA) for the hydrocarbon sector.